Maximum weight record of fruit carried by Artibeus fraterculus - Carrasco-Escudero, Luiggi; Jara, Mario; Hughes, Morgan (Therya Notes, 2025)
Artibeus fraterculus Anthony, 1924 is a fruit bat of the family Phyllostomidae, endemic of the Tumbesian region of Ecuador and Perú. This study was carried out in 2 localities of Cajamarca, Matibamba and Cangrejo, in the Seasonally Dry Forest of the Marañón, in the region of Cajamarca, Peru. Their feeding behavior was documented and fruits found in natural feeding roosts were analyzed. During the observations, the bats consumed fruits such as guava (Psidium guajava), loquat (Eriobotrya japonica), plum (Spondias purpurea) and mango (Mangifera indica). Notably, an individual was observed carrying a guava fruit whose weight was estimated to be 105.88 % of the bat's body weight. These observations suggest that A. fraterculus plays a crucial role as a seed disperser of economically important and relatively large fruit, especially in disturbed landscapes. This work also expands existing knowledge on the diet of this species by including S. purpurea and describes specific foraging behaviors in relation to feeding roosts. Insights gained from this work highlight how direct observations and analysis of fruits at feeding sites complements other approaches such as fecal analysis, providing valuable information on the feeding ecology and activity patterns of A. fraterculus.